Survei Sarana dan Prasarana Pendidikan Jasmani di Sekolah Menengah Atas Negeri Se-Kabupaten Magelang - Ainul Yaqqin, Muhammad Jody; Irsyada, Roas (Indonesian Journal for Physical Education and Sport, 2023)
The background of this research is the limited physical education facilities and infrastructure at public high schools in Magelang regency. The research objective was to determine the availability and condition of physical education facilities and infrastructure in public high schools throughout Magelang regency. The population used in this study consisted of 10 public high schools in Magelang regency. The selection of samples using the Accidental Sampling technique obtained 5 samples of public high school physical education teachers in Magelang Regency. The instruments used are observation, interviews with physical education teachers, observation sheets, and documentation. The results of the research on the availability of physical education facilities for state high schools in Magelang Regency show that 5 schools are in the good category (100%). The availability of physical education infrastructure for public high schools in Magelang Regency is 3 schools that are in the good category (60%), there are 2 schools that are in the sufficient category (40%). The condition of public high school physical education facilities in Magelang Regency is as much as (88.10%) feasible and as much as (11.90%) is not feasible. The condition of physical education infrastructure for state high schools in Magelang Regency is as much as (87.9%) feasible and as much as (12.1%) is not feasible. From the results of the research above, it can be concluded that the availability and condition of physical education learning facilities and infrastructure in SMA Negeri throughout Magelang Regency is sufficient.